Substance and methods of forecasting of technogenic risk - Белов, П. Г.; Запорожченко, Ю. Ф. (Proceedings of National Aviation University (archive), 1999)
Considered are the different approaches to interpretation and quantitative evaluation of technogenic risk. Given is adequate interpretation of danger and risk. Proposed is the common methodology of forecasting and prior evaluation of technogenic risk